The modelling by finite elements of plane junction zones in heat transfer problems - Turskienė, Sigita (Lietuvos matematikos rinkinys, 2000)
The paper deals with the temperature field analysis problem of the junction zone of the thin-walled branched structures plates, which is important for the investigation of thermal stress concentration zones.